2018
DOI: 10.6000/1929-4247.2018.07.02.3
|View full text |Cite
|
Sign up to set email alerts
|

Project Spraoi: Dietary Intake, Nutritional Knowledge, Cardiorespiratory Fitness and Health Markers of Irish Primary School Children

Abstract: Objective: Examine dietary intake (DI), anthropometric measures, cardiorespiratory fitness (CRF) and nutritional knowledge (NK) of school children. Design: Cross-sectional study. Food Diary, NK questionnaire and 550m walk/run test were used to assess DI, NK and CRF respectively. Blood pressure (BP) was also taken and body mass index (BMI) and waist to height ratio (WHtR) were calculated. Setting: Two primary schools, Cork, Ireland. Subjects: Six (n = 49, age 5.9 ± 0.6 years) and ten (n = 52, age 9.8 ± 0.5 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 35 publications
1
6
0
1
Order By: Relevance
“…Project Spraoi is based on Project Energize, which has been implemented in New Zealand since 2004, and proven to be successful and cost-effective (62) . Initial findings from Project Spraoi research (28) indicate that the intervention has the potential to improve the health of children in Ireland, which supports recent policy (63) . Preventing children from becoming overweight and obese is the best approach and this is the focus of Project Spraoi, which aims to make healthy eating and increased PA a daily habit.…”
Section: Public Health Implicationssupporting
confidence: 56%
See 4 more Smart Citations
“…Project Spraoi is based on Project Energize, which has been implemented in New Zealand since 2004, and proven to be successful and cost-effective (62) . Initial findings from Project Spraoi research (28) indicate that the intervention has the potential to improve the health of children in Ireland, which supports recent policy (63) . Preventing children from becoming overweight and obese is the best approach and this is the focus of Project Spraoi, which aims to make healthy eating and increased PA a daily habit.…”
Section: Public Health Implicationssupporting
confidence: 56%
“…Whereas 56.9% of 10 year olds had normal BP, 27.5% had high-normal and 15.7% had high BP. Intakes of calcium, iron and fibre were below recommended levels and sodium and saturated fat intakes were also higher than recommended 28 . As previous research 28 found no statistical differences between genders, results for boys only and girls only were not included in this manuscript's statistical inference.…”
Section: Baseline Anthropometric and Dietary Intake Datamentioning
confidence: 75%
See 3 more Smart Citations